Marina Abramovic - Richards, Mary (Mary Elizabeth), 1966- (London : Routledge, 2010)
Marina Abramovic's legendary performances have earned her the title of 'The Grandmother of Performance Art'. Her extreme and challenging pieces focus on the relationship between the performer and their audience, and the role of the body and the mind in performance art.
Includes bibliographical references and index.
boek
Keywords: Abramovic, Marina -- Criticism and interpretation